The Importance Of Distinguishing Between The Global Crime And The International Crime - أحمد بسام; ميكائيل تميم (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The Crime of any kind and its name constitutes a sinful assault on higher human interests. The scientific progress achieved، especially in the field of communications and transportation، has contributed to the crime exceeding the boundaries of a single state to reach many countries، and the Criminality becomes global، and the crime becomes global. Criminals have exploited the fruits of progress by employing it in their cooperation in crime by forming organized associations and gangs whose dangers go beyond the nation-state، to infect the entire international community، yet in their essence they remain ordinary crimes، even if they are committed on an international scale، then they are a global crime، and not an international crime، because individuals commit it in their own capacity and not as representatives of their countries acting in their name and account، International crimes are the most dangerous to international relations، because they violate humanitarian principles and threaten international peace and security، because they are committed in the name of the state، and the state is a political and legal institution that represents the finest human societies. This criminal behavior is often adopted by the dominant countries to subjugate the peoples who defend their freedom and independence. The legal concept of global crime differs from the concept of international crime with the consequent important results in the relations between states، and this is what we will highlight through this research.